PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DAN PENDAPATAN ASLI DAERAH (PAD) KOTA BALIKPAPAN - Rosmalia, Johana; Iskandar, Rusdiah; Fitriadi, Fitriadi (Journal of Innovation in Business and Economics, 2014)
This study used secondary data in the form of time series which are analyzed using Pathway analysis with multiple linear regression formula. The purpose of this study was to determine the effect of investment and labor to gross regional domestic product (GRDP) and regional revenues in Balikpapan city.  The results of the study was shown that Y = 0.202 - 0.098 X1 + 0.244 X2 + 0.825 X3. The results showed that investment, labor and gross regional domestic product (GRDP) have jointly effect on the regional revenues in Balikpapan city. Partially; the investment has no significant effect on gross regional domestic product (GRDP), labor has significant effect on gross regional domestic product (GRDP), gross regional domestic product (GRDP) has significant effect to regional revenues in Balikpapan city, the investment has no significant effect on regional revenues in Balikpapan city, and labor has no significant effect on regional revenues in Balikpapan city. The contribution of investment, labor and gross regional domestic product (GRDP) variable was about 93.5 % and it means that those have very strong relationship; meanwhile, the rest, about 6.5 %, has been influenced by other factors.